2012
DOI: 10.1016/s1470-2045(12)70377-7
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib after induction for treatment of children and adolescents with Philadelphia-chromosome-positive acute lymphoblastic leukaemia (EsPhALL): a randomised, open-label, intergroup study

Abstract: SummaryBackgroundTrials of imatinib have provided evidence of activity in adults with Philadelphia-chromosome-positive acute lymphoblastic leukaemia (ALL), but the drug's role when given with multidrug chemotherapy to children is unknown. This study assesses the safety and efficacy of oral imatinib in association with a Berlin–Frankfurt–Munster intensive chemotherapy regimen and allogeneic stem-cell transplantation for paediatric patients with Philadelphia-chromosome-positive ALL.MethodsPatients aged 1–18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
233
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(247 citation statements)
references
References 31 publications
5
233
2
7
Order By: Relevance
“…38,39 Subsequently, several studies explored the efficacy of incorporating imatinib into frontline chemotherapy regimens. 15,16,19,[40][41][42][43][44] In one of the first clinical trials combining imatinib with chemotherapy (the hyperCVAD regimen), we reported a complete remission rate of 100% in patients treated with active disease and a 2-year DFS rate of 85%. 17 There were no unexpected toxicities from the addition of imatinib mesylate to the regimen and the outcomes were superior to historical outcomes with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Subsequently, several studies explored the efficacy of incorporating imatinib into frontline chemotherapy regimens. 15,16,19,[40][41][42][43][44] In one of the first clinical trials combining imatinib with chemotherapy (the hyperCVAD regimen), we reported a complete remission rate of 100% in patients treated with active disease and a 2-year DFS rate of 85%. 17 There were no unexpected toxicities from the addition of imatinib mesylate to the regimen and the outcomes were superior to historical outcomes with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…14 For infants and patients with bcr-abl rearrangement after 2005, indications of HSCT were as described in the INTERFANT and ESPHALL trials. 15,16 Patients with relapsed ALL were treated according to the risk stratification of BFM relapses protocols. 17 For AML patients in CR1, HSCT was recommended for all patients with monosomy 5 or 7, translocation t(6,9) and mixed lineage leukemia rearrangement, except for translocation t(9,11) with related or unrelated donors, and was performed in other cases with matched sibling donors (MSDs) only, except for patients with translocation t (8,21).…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…103 The paradigm for precision medicine in leukemia is the use of ABLclass TKIs in chronic myeloid leukemia and combination therapy with TKIs and chemotherapy in Ph1 ALL. 104,105 Although important questions remain in Ph1 ALL (including the optimal TKI, the optimal chemotherapy backbone, the length of TKI therapy, the role of allogeneic hematopoietic stem cell transplantation in first remission, and the role of TKIs after hematopoietic stem cell transplantation), any patient diagnosed with Ph1 ALL in the United States or western Europe will receive a TKI as part of therapy. There is consequently enthusiasm to extend TKI therapy to Ph-like ALL, but it is critical to determine whether kinase-activating alterations are similar drivers to BCR-ABL1; that is, to show that they arise early in disease development, that they are present in all subclones at all stages of disease, and that the leukemia is dependent upon continued activity of the mutant kinase.…”
Section: Prospects For Precision Medicine In Allmentioning
confidence: 99%